2014
DOI: 10.1155/2014/925805
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Analysis of Inflammatory Markers in Discoid Lupus Erythematosus Skin

Abstract: Prior studies identified T cells, B cells, and macrophages in the inflammatory infiltrate and up-regulation of their protein products in discoid lupus erythematosus (DLE) skin; however, they lacked rigorous analyses to define their specific locations in skin. Thus, we compared expressions of selected T cell, B cell, and macrophage markers in five areas of DLE, psoriasis, and normal skin. Immunostainings for CD3, CD4, CD8, CD20, CD68, CXCR3, CXCL10, and TIA-1 were performed in biopsies of 23 DLE lesional skin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Primary sclerosing cholangitis is characterized by chronic bile duct destruction and inflammation and has been consistently associated with other liver and biliary tract cancers . Mechanisms for the associations with ankylosing spondylitis, aplastic anemia, celiac disease, discoid lupus erythematosus and vitiligo may include immunological, genetic and inflammatory pathways . For example, celiac disease, which causes inflammation in the small intestine, could potentially lead to carcinogenic changes in the ampulla of Vater, located in the duodenal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Primary sclerosing cholangitis is characterized by chronic bile duct destruction and inflammation and has been consistently associated with other liver and biliary tract cancers . Mechanisms for the associations with ankylosing spondylitis, aplastic anemia, celiac disease, discoid lupus erythematosus and vitiligo may include immunological, genetic and inflammatory pathways . For example, celiac disease, which causes inflammation in the small intestine, could potentially lead to carcinogenic changes in the ampulla of Vater, located in the duodenal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies examining their interactions and impact on evolution of DLE will be planned. As DLE skin is enriched with multiple types of immune cells [ 13 , 46 ], our qRT-PCR data demonstrated that DLE skin upregulates cell surface markers expressed by dendritic cells (CD86) and monocytes (CD14), which can also express M1 macrophage-related proteins (e.g., CXCL10 [ 47 , 48 ] and ISG15 [ 49 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced B cell infiltration appears to be accompanied by CD3 + , CD4 + , and CD8 + T cells (36). Moreover, B cells organize into aggregates, closely associated with CD3 + T cells (37). Nests of B cells and plasma cells in close proximity to T cells are also found in the lesional skin of patients with LE panniculitis (38) potential role of these lymphoid aggregates in cutaneous lupus has not been evaluated, and it is unknown if these structures produce antigen-specific B cells or pathogenic antibody (Figure 2).…”
Section: The Pathogenic Role Of Cutaneous B Cells In Human Diseasementioning
confidence: 98%